PREPARATION ASSISTANCE OF HOTS-BASED THEMATIC QUESTIONS FOR STUDENTS OF PRIMARY SCHOOL TEACHER EDUCATION (PGSD) PROGRAMME - Sumarah, Ignatia Esti; Kencana, Cipta Gilang (Sanata Dharma University Yogyakarta, 2022)
Based on the results of the mid-semester exams of Primary School Teacher Education (PGSD) students class of 2019 (class 6B and 6C) of Sanata Dharma University, researcher get data if they still have difficulty in making HOTS-based thematic questions. Therefore, the researcher collaborated with 4th grade teacher of Santa Angela Elementary School Bandung (graduated from S2 Biology Education, Universitas Pendidikan Indonesia) to provide online assistance to students through high-end integrated learning courses (which is mastered by researcher). This research is a narrative research to describe (1) the strategy of preparing HOTS-based thematic questions in 4th grade Elementary Schools, (2) infographic analysis of HOTS-based thematic questions compiled by students, (3) the results of the trial of the infographic of these questions to 4th grade students of Santa Angela Elementary School Bandung.